Pengaruh Edukasi 1000 Hari Pertama Kehidupan (HPK) Terhadap Pengetahuan Dan Sikap Wanita Usia Subur (WUS) - Hidayati, Diah Ulfa; Yulastini, Fitria; Fajriani, Evalina (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2022)
Introduction: Indonesia's health development still facing various challenges, one of which is the high incidence of stunting in children under five. Based on a preliminary study conducted in Perina Village, Jonggat District, Central Lombok Regency, mothers' knowledge and attitudes about caring for the first 1000 days of life (HPK) were still low. The low knowledge and attitude of mothers about nutrition in 1000 HPK can lead malnutrition conditions that occur since in the womb and early period after birth so it can affect growth and development problems in the future. The government has promoted the